WASTE RECYCLING: AN IMPORTANT ENVIRONMENTAL ISSUE AND PROPOSED MEASURES (European Journal of Economics, Finance and Business Development, 2025)
Waste recycling has become a critical environmental issue in the modern world due to the rapid increase in waste generation and its adverse impact on ecosystems. The improper disposal of waste contributes significantly to pollution, resource depletion, and climate change. This paper explores the importance of waste recycling as a solution to reduce waste accumulation and promote environmental sustainability. The research emphasizes the benefits of recycling, such as resource conservation, energy savings, and reduced environmental pollution.